Drug Interactions in Coronary Heart Disease Patients : a Literature Review - Tamarah, Elok; Handayani, Handayani; Ferdiantoro, Andik (Jurnal Medis Islam Internasional, 2022)
Background: Patients with coronary heart disease generally receive many drugs, such as hypercholesterolemia, antianginal, antiplatelet, anticoagulants, and medications for comorbid illnesses such as antihypertension and diabetes mellitus. Concomitant administration of several types of drugs may result in drug interactions. Objective : This study aims to figure out drug interactions that might occur in using combination drugs in patients with coronary heart disease. Methods: This article review uses the Google Scholar database, published 2017-2022. The keywords used were "coronary heart disease and drug interactions." The PRISMA flowchart is used to summarize the article selection process. Results: Administration of aspirin  with  clopidogrel  causes  a  moderate  synergistic  interaction,  whereas  administration  of antiplatelet agents with anticoagulants causes a significant synergistic interaction on bleeding. And the administration of  nifedipine  with  atorvastatin causes  a  synergistic  pharmacodynamic interaction. Conclusions: Drug interactions occur in patients with coronary heart disease, either synergistic or antagonistic pharmacodynamic interactions with minor, moderate, and significant classifications